Effect of physical activity and sedentary sitting time on psychological quality of life of people with and without disabilities; A survey from Saudi Arabia - Zahra, Aqeela; Hassan, Sehar-un-Nisa; Hassan, Muhammad Shehzad; Parveen, Nuzhat; Park, Jae-Hyun; Iqbal, Naveed; Khatoon, Fahmida; Atteya, Mohamed Raafat (Frontiers in Public Health, 2022)
Background: Mental and psychological health issues are on the rise globally. People with disabilities are at greater risk of poor psychological quality of life especially after covid-19 pandemic. Along with other factors physical activity (PA) may have a significant effect on mental health. This study aims to analyze the difference of PA participation and sitting time among people with and without disabilities and their association with psychological quality of life. Methods: A standard questionnaire was used to collect the data from disabled and non-disabled participants above 15 years of age. Bivariate and multivariate analysis was performed to yield statistical results. Results: Total study sample consisted of 359 participants (67.7% without disability and 32.3% with disability). Participants without disabilities reported a significantly better psychological QOL (Mean score=68) as compared to the ones with disabilities (Mean score=61), (p<0.01).There was significant difference between the sitting time of two groups with longer sitting time among people with disabilities (6.1h/day) as compared to non-disabled (5.3h). Optimum level of PA was strongly associated with better psychological quality of life among individuals without disabilities (p=0.00). Younger age (p=0.00) and being single (p=0.01) were significant predictors of poor psychological health among non-disables. Increase in sedentary sitting time was significantly associated with poor psychological quality of life among both groups. Conclusions: Tailored health policies to encourage PA and reduce sitting hours should be formulated to improve psychological health with special focus on individuals with disabilities. Future studies with large sample size are recommended to validate the current results and further explore the difference in association of PA and psychological wellbeing in people with and without disabilities.